2010
DOI: 10.1002/ep.10354
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of psychrophiles in improving bio‐treatment efficiency of small size constructed wetlands during cold weather

Abstract: Constructed wetland technique for waste water treatment has many advantages, including high treatment efficiency, low investment and energy cost, and easy operation and maintenance. However, the inhibitive effect of low temperature on treatment efficiency remains a serious problem in cold weather for many small size wetlands. In this study, the application of cold-tolerating bacteria in maintaining the nitrogen waste treatment efficiency of small size constructed wetland during cold weather was investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In recent years, CWs have been widely used in wastewater treatment, including removal of N, P (Li et al, 2019), and some organic contaminants. Nevertheless, due to restricted oxygen supply and transport capacity, limited sorption capacity of the substrate, and inhibition of microbes and plants metabolism at low temperatures, the removal efficiency for N and P is severely hindered (Ying et al, 2010). Researchers have attempted to explore particular substrates to intensify the functions of CWs with high contaminants concentration, among which biochar has been favorably considered (Gupta, Prakash & Srivastava, 2015).…”
Section: Indirect Water and Wastewater Treatmentmentioning
confidence: 99%
“…In recent years, CWs have been widely used in wastewater treatment, including removal of N, P (Li et al, 2019), and some organic contaminants. Nevertheless, due to restricted oxygen supply and transport capacity, limited sorption capacity of the substrate, and inhibition of microbes and plants metabolism at low temperatures, the removal efficiency for N and P is severely hindered (Ying et al, 2010). Researchers have attempted to explore particular substrates to intensify the functions of CWs with high contaminants concentration, among which biochar has been favorably considered (Gupta, Prakash & Srivastava, 2015).…”
Section: Indirect Water and Wastewater Treatmentmentioning
confidence: 99%
“…In recent years, CWs have been widely used in wastewater treatment, including removal of N, P (Li et al, 2019), and some organic contaminants. Nevertheless, due to restricted oxygen supply and transport capacity, limited sorption capacity of the substrate, and inhibition of microbes and plants metabolism at low temperatures, the removal efficiency for N and P is severely hindered (Ying et al, 2010). Researchers have attempted to explore particular substrates to intensify the functions of CWs with high contaminants concentration, among which biochar has been favorably considered (Gupta et al, 2015).…”
Section: Indirect Water and Wastewater Treatmentmentioning
confidence: 99%
“…A large number of microorganisms will be lost, making it di cult to control its long-term treatment effect. As a result, it is found that the function of two or more microbial strains to combine the dominant strains has a better synergistic effect than a single strain (Tang et al 2018;Ying et al 2010). In previous research, Ying et al (Ying et al 2010)explored the ammonia nitrogen removal rates of the three cold-resistant strains into the constructed wetland system in cold areas to remove the winter wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the isolated strains were Psychrotrophic bacteria (Westlake et al 1974;Atlas 1981;Järvinen, Melin, and Puhakka 1994;Yao et al 2013;Vacková, Srb, and Stloukal 2011), the molecular mechanism and related theory of its low temperature adaptability has also been studied. (Järvinen, Melin, and Puhakka 1994;Guo et al 2010;Ma et al 2009;Ying et al 2010). Pei et al (Pei, Yang, and Tian 2010) studied the effect of Bacillus.Subtilis FY99-01 on denitri cation e ciency in wetlands and showed that the addition of microbial strain could effectively increase the nitrate removal e ciency in wetlands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation